Computational stress and modal analysis of automobile tyre - Iskandar Izany, A Rahman (2008)
All of bodies exist in the world may tent to failure because of stress and vibration. Tires are the only components of a vehicle in contact with the road. The interaction between the tire and road generates the forces and vibration. This paper summarizes systematically the behavior of the tire by simulated using finite element method. The objective of this project is to analyze the stress and modal analysis of the tire. The tire modeled in Computer Aided Design (CAD) using SolidWork software. ALGOR software from Computer Aided Engineering (CAE) will be analyzed the tire model. In the stress analysis, the force was assumed to be vertical (z-direction) reaction force generated at the tire contact patch. The contact patch dimensions were assumed about a central angle of 300 from either side of the point of contact with the ground. The tire was applied a vertically force with 1000 N until 5000 N. According to the analysis is expected that the contact patch and belt edge separation receive high stress concentration. The values of the maximum Stress Von Misses are about 0.872322 until 4.54497 N/mm2. The maximum values for stress are increasing when the forces applied are increased. The natural frequency analysis from FEA was compared to the experimental data. Result shows that 1st natural frequency (57.9038 Hz), 2nd natural frequency (65.1867 Hz), 3rd natural frequency (65.7771 Hz) and 4th natural frequency (70.8319 Hz). Through this project, there will be no big different value for both methods. The percentage of error is around 30% from the experimental result. Finally it can be conclude that, in order to obtain the behavior of the tire such as stress and vibration, stress and modal analysis can be carried out. Reducing the vibration and stress will be very useful and enhance a good quality of riding. Once the tire lack, the overall part of the car will be affected.